EXPLORING THE RELATIONSHIP BETWEEN INTERCULTURAL SENSITIVITY AND LANGUAGE LEARNING MOTIVATION: A STUDY ON EFL UNDERGRADUATE STUDENTS AT A VIETNAMESE UNIVERSITY - Nguyen, Huyen-Thanh (VNU Journal of Foreign Studies; Vol 38 No 6, 2022)
This research was conducted to investigate the relationship between intercultural sensitivity and language learning motivation among EFL undergraduate students at Hanoi University, a public higher education institution in Hanoi, Vietnam. The findings revealed a positive correlation between intercultural sensitivity and language learning motivation as EFL students had high levels of both factors, yet students seemed to lack confidence in intercultural communication. It is suggested that the teacher should communicate with EFL students about the importance of intercultural communicative competence, intercultural sensitivity, and language learning motivation. Besides, the course on intercultural sensitivity should also be embedded in the curriculum.